Quality of life in ambulatory pulmonary arterial hypertension in connective tissue diseases and its relationship with risk stratification. (1st July 2021) - Shi, Yue; Meng, Yanling; Dong, Xingbei; Liu, Yang; Liu, Yongtai; Lai, Jinzhi; Tian, Zhuang; Zhao, Jiuliang; Peng, Jinmin; Wang, Qian; Li, Mengtao; Zeng, Xiaofeng
Abstract : The Pulmonary Arterial Hypertension Symptoms and Impact Questionnaire (PAH‐SYMPACT) is a PAH‐specific patient‐reported outcome scale assessing patients' quality of life from four aspects: cardiopulmonary symptoms, cardiovascular symptoms, physical impacts and cognitive/emotional impacts. This study aimed to validate the Chinese version of PAH‐SYMPACT and explore its relationship with risk stratification in patients with connective tissue disease‐associated pulmonary arterial hypertension (CTD‐PAH). In addition, 75 patients with CTD‐PAH confirmed by right heart catheterization were invited to complete questionnaires including PAH‐SYMPACT, the 36‐item Medical Outcomes Study Short Form Survey (SF‐36) and EuroQol five dimensions questionnaire (EQ‐5D). The demographic, clinical, laboratory and treatment data were collected. The endpoint was treatment goal achievement status in 6–12 months after completing the questionnaires, defined as an integrated outcome. Participants' mean age was 36.4 ± 11.9 years and the mean pulmonary arterial pressure was 38.9 ± 13.67 mmHg. The reliability of the PAH‐SYMPACT domains ranged from 0.83 to 0.88. Results of factor analysis basically conformed the original PAH‐SYMPACT. The treatment goal achievement (TGA) status in 6–12 months was significantly associated with physical impacts scores (odds ratio: 0.180, 95% confidence interval: 0.036–0.908, P=0.038). The Chinese version of PAH‐SYMPACT is a reliable measurement to evaluate quality of life in CTD‐PAH patients and is also a potential predictor of patient's condition change in routine clinical practice.